2010
DOI: 10.1159/000282113
|View full text |Cite
|
Sign up to set email alerts
|

Serum Anti-Müllerian Hormone Concentrations in Prepubertal Girls with and without Premature Adrenarche: The Influence of Body Mass Index

Abstract: Background: A connection between premature adrenarche (PA) and polycystic ovary syndrome (PCOS) has been proposed. We investigated whether anti-müllerian hormone (AMH) production is increased in prepubertal girls with PA, as it is in women with PCOS and in their prepubertal daughters. Methods: Fifty-two prepubertal girls with PA and 48 prepubertal age-matched controls were studied. Serum AMH concentrations were determined by a specific ELISA assay and correlated with baseline steroid hormone, GnRH-stimulated L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
0
9
1
Order By: Relevance
“…Increased AMH concentrations were observed in adolescent girls with PCOS and in prepubertal and peripubertal daughters of PCOS women when compared to respective controls. 32,33 In a recent study, Utriainen et al 34 did not find serum AMH levels in prepubertal girls with PA to be indicative of PCOS-related abnormalities. However, in a cohort of Scottish children with PA, Paterson et al 35 found AMH levels to be higher than in controls.…”
Section: Discussionmentioning
confidence: 92%
“…Increased AMH concentrations were observed in adolescent girls with PCOS and in prepubertal and peripubertal daughters of PCOS women when compared to respective controls. 32,33 In a recent study, Utriainen et al 34 did not find serum AMH levels in prepubertal girls with PA to be indicative of PCOS-related abnormalities. However, in a cohort of Scottish children with PA, Paterson et al 35 found AMH levels to be higher than in controls.…”
Section: Discussionmentioning
confidence: 92%
“…A number of studies have evaluated the association between AMH and BMI [11,[14][15][16][17][18][19][20][27][28][29][30][31]. (Table 4) These study results can be classified under two groups: (1) studies which suggest presence of a negative correlation between AMH levels and BMI, (2) studies which suggest that there is no correlation between BMI and AMH levels.…”
Section: Discussionmentioning
confidence: 99%
“…Early pubarche develops as a result of premature production and release of adrenal androgens, and may be an indicator of PCOS 8 . Based on the hypothesis that AMH may be an indicator of a potential PCOS in individuals with early pubarche, a study on prepubertal girls with early adrenarche found lower serum AMH levels in this population compared to the controls, not supporting this hypothesis 4 . In our study, the subjects in group 2 and the control group did not differ significantly and the subgroup analysis did not result in any relevant differences between group 1, group 2, group 3 and control group regarding the AMH levels.…”
Section: Discussionmentioning
confidence: 68%
“…Women with PCOS were shown to have higher AMH levels compared to healthy women. Different studies have also reported higher AMH levels in prepubertal and peripubertal daughters of women with PCOS [4][5][6] . These reports suggest that changes in AMH production associated with PCOS may be observed even during the prepubertal period.…”
mentioning
confidence: 95%
See 1 more Smart Citation